2021
DOI: 10.1101/2021.07.26.21250865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cash versus Lotteries: COVID-19 Vaccine Incentives Experiment*

Abstract: Governments are considering financial incentives to increase vaccine uptake to end the COVID-19 pandemic. Incentives being offered include cash-equivalents such as vouchers or being entered into lotteries. Our experiment involved random assignment of 1,628 unvaccinated participants in the United States to one of three 45 second informational videos promoting vaccination with messages about: (a) health benefits of COVID-19 vaccines (control); (b) being entered into lotteries; or (c) receiving cash equivalent vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…An online RCT found that a news story communicating the personal health risks of not getting vaccinated, and another communicating the collective public health consequences of not getting vaccinated, increased vaccination intention [ 18 ]. Another online RCT (pre-print), measuring a digital expression of interest, found that after watching a video promoting the health benefits of the COVID-19 vaccine, 16% of unvaccinated participants wanted more information [ 19 ]. This proportion of participants was similar to those who watched a video including the promotion of cash lotteries, although less effective than a video promoting states using cash vouchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An online RCT found that a news story communicating the personal health risks of not getting vaccinated, and another communicating the collective public health consequences of not getting vaccinated, increased vaccination intention [ 18 ]. Another online RCT (pre-print), measuring a digital expression of interest, found that after watching a video promoting the health benefits of the COVID-19 vaccine, 16% of unvaccinated participants wanted more information [ 19 ]. This proportion of participants was similar to those who watched a video including the promotion of cash lotteries, although less effective than a video promoting states using cash vouchers.…”
Section: Resultsmentioning
confidence: 99%
“…An online experiment (pre-print) found that adding educational videos to reminders to schedule COVID-19 vaccines increased the effectiveness of a reminder and led to an increase in participants reported likelihood of scheduling an appointment [ 16 ]. An online RCT (pre-print) found that 22% of unvaccinated respondents expressed wanting further information on the vaccine after watching a video containing information on the health benefits of the vaccine and a cash voucher incentive for vaccination, compared to 14–16% for a video with lottery incentives or a standard information video without an incentive, respectively [ 19 ]. An online RCT (pre-print) found that only a male-narrated video providing details about the COVID-19 vaccine and emphasising the altruistic motivations associated with vaccination increased intention [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that video messages had a more negligible effect on the vaccination rate than text messages ( 25 ). On the other hand, messages regarding cash vouchers raised people's willingness to get information about vaccination; however, it is unclear how much this intervention will actually lead to getting vaccinated ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, financial incentives have been found to increase vaccine uptake in several countries (e.g., the U.S., Kenya, Australia) targeting a variety of infections including Human Papillomavirus, Measles, Polio, and Hepatitis B ( Caskey et al, 2017 , Gibson et al, 2019 , Kagucia et al, 2021 , Mantzari et al, 2015 ). Studies in the U.S., Germany, and Sweden found that hypothetical incentives increased COVID-19 vaccination intentions ( Carpio et al, 2021 , Duch et al, 2021 , Klüver et al, 2021 , Sprengholz et al, 2021 ). Each of these studies was structured differently, with the largest range offered being 0 to 10,000 Euros.…”
Section: Introductionmentioning
confidence: 99%